Sosial budaya yang berpengaruh Terhadap Minat Membaca Mahasiswa Unmer Malang - Lia Nasikhatul; Sahiruddin Sahiruddin; Ismatul Khasanah (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2020)
AbstractThis study analyzes socio-cultural factors on the literacy ability of reading students at the Merdeka University of Malang. The purpose of this research is to examine the socio-cultural aspects that also influence students' reading interest and reading ability. The approach in this study is qualitative. The qualitative approach is used to answer the third objective in the form of descriptive socio- cultural factors. Participants in this study were 53 students of Merdeka Malang University. Data was collected from the results of the UKBI test and reading interest questionnaire and socio-cultural factors for students. Socio-cultural factors that affect student literacy are literacy culture and reading interest developed from childhood at the family, environment, school and government institutions. The ability to read literacy must look at the whole, from the aspects that exist in the reader and outside factors. Socio-cultural factors that influence the reading literacy of students include socioeconomic factors of the family, the level of parental education, financial position, the role of the government in promoting reading literacy, supporting book supply facilities. This research shows that reading ability is related to knowledge of sentence structure. The better the students' reading skills, the better the reading test scores. However, the factors that contribute to literacy beyond the knowledge of sentence structure need to be studied in further research.Keywords: Reading Literacy, Reading Interest, Social Factors  AbstrakPenelitian ini menganalisis tentang faktor sosial budaya terhadap kemampuan literasi membaca mahasiswa Universitas Merdeka Malang. Tujuan penelitan ini adalah mengkaji aspek sosial budaya yang turut mempengaruhi minat baca dan kemampuan membaca mahasiswa. Pendekatan dalam penelitian ini bersifat kualitatif. Adapun pendekatan kualitatif digunakan untuk menjawab tujuan ketiga berupa deskriptif faktor sosial budaya. Partisipan dalam penelitian iniadalah mahasiswa Universitas Merdeka Malang yang berjumlah sebanyak 53 mahasiswa. Data dikumpulkan dari hasil test UKBI dan angket minat baca dan faktor sosial budaya untuk mahasiswa. Faktor sosial budaya yang berpengaruh pada literasi membaca mahasiswa adalah budaya literasi dan minat baca yang dikembangkan dari masa kecil di tingkat keluarga, lingkungan, sekolah dan institusi pemerintahan. Kemampuan literasi membaca haruslah melihat secara menyeluruh, dari aspek yang ada pada diri pembaca dan faktor yang diluarnya. Faktor sosial budaya yang berpengaruh pada literasi membaca mahasiswa meliputi faktor sosial ekonomi keluarga, tingkat pendidikan orangtua, posisi finansial, peran pemerintah dalam menggalakkan literasi membaca, fasilitas pasokan buku yang menunjang. Penelitian ini menunjukkan faktor yangberkontribusi terhadap literasi membaca di luar faktor pengetahuan struktur kalimat perlu dikaji lebih dalam pada penelitian selanjutnya.Kata Kunci: Literasi Membaca, Minat Baca, Faktor Sosial